Femtocell Network Time Synchronization Protocols and Schemes - Hasan, M.K.; Saeed, Rashid A.; Hassan Abdalla Hashim, Aisha; Islam, Shayla; A. Alsaqour, Raed; A. Alahdal, Tariq (Maxwell Scientific Organization, 2012, 2012)
The femtocell network allows connecting to cellular network through broadband connection. In femtocell, time with network synchronization becomes a critical issue at present. Synchronization is a process which is required in the femtocell network due to the shortcomings of centralized coordination between a number of femtocell Base Station (fBS) and clock synchronization server. Time synchronization procedure allows exchanging message that contains timestamp and delay measurement. There are several time synchronization protocols and algorithms based on precision which are Network Time Protocol (NTP), Simple Network Time Protocol (SNTP), IEEE 1588 Timing Protocol, enhancement of IEEE 1588 timing and receiverreceiver synchronization scheme. In this study, we investigated some of the time synchronization protocols and schemes for femtocell network. In addition, we proposed intra-cluster synchronization scheme to minimize the clock offset and skew for better synchronization accuracy. The proposed scheme is able to perform precise synchronization for clock offset and clock skew than the existing receiver-receiver synchronization scheme.